Towards Efficient and Reliable Video Communication: A Survey on Scalability, Error Protection, and Multicasting - Wijesekara, Patikiri Arachchige Don Shehan Nilmantha (AI Society & STMIK Indonesia, 2025)
Efficient and reliable video communication is required to maintain high-quality and uninterrupted streaming in order to minimize bandwidth usage and to tackle network variability. Scalable Video Coding (SVC) introduces efficiency for video communication by introducing a base layer and a set of enhancement layers, while Unequal Error Protection (UEP) can provide high protection to important layers while having low redundancy for less important layers/bits/frames. Moreover, scalable video transmission’s efficiency can be further improved by multicasting a video to multiple recipients simultaneously over a network efficiently, where each user can adapt to network conditions. As existing surveys do not concentrate on discussing the improving efficiency and reliability of video communication by multicasting scalable video communication focusing on UEP, we review these factors individually and in combination. We first gathered 113 original research studies using qualification criteria searched using electronic libraries, leveraging an elaborative process. As per the review, video scalability has been achieved using temporal scalability, spatial scalability with spatial resolution, quality scalability using quantization steps, and slice grouping for region of interest scalability, while UEP is achieved using transceiver, packet level, bit level, and cross-layer methods. Moreover, simulcast, multiple access techniques, multi-resolution modulation, and antenna heterogeneity have shown to be the promising SVC multicasting techniques. Review analysis shows that from reviewed work, 10.3% provide H.265-based scalability, 19.2% use transceiver UEP, and 7.7% use simulcast. Finally, we conclude our review by discussing the advantages and challenges of the concept of SVC-UEP video communication and then presenting guidance to overcome them.